Comparison of antiviral effect of oxidizing disinfectants against murine norovirus-1 and hepatitis A virus on fresh root vegetables. (June 2021) - Kim, Mi Rae; Han, Sangha; Park, Sa Reum; Moon, Yoah; Ha, Sang-Do
Abstract: This study compared the effectiveness between sodium hypochlorite (NaOCl) and its alternatives—chlorine dioxide (ClO2 ) and peroxyacetic acid (PAA)—against murine norovirus-1 (MNV−1) and hepatitis A virus (HAV) contamination on carrot and lotus root. ClO2 treatment at 123–300 and 170–300 ppm for 3 min reduced MNV-1 by 1–2.51 log PFU/mL (carrot) and 1–1.83 log unit (lotus root), respectively. ClO2 treatment at > 270 ppm also achieved >1 log HAV reduction for both samples, and PAA treatment at 180–500 and 280–500 ppm for 3 min decreased MNV-1 and HAV by 1–3 and 1–2 log units, respectively. NaOCl showed the lowest antiviral effect among the three disinfectants. Enteric viruses were more difficult to inactivate on lotus root than carrot because of the starch as organic matter. No significant differences ( P  > 0.05) in the physicochemical qualities (surface color, hardness, pH) of carrot and lotus root were observed after treatment, even at the maximum concentration applied. Such findings suggest the use of 270 ppm ClO2 or 280 ppm PAA in the fresh root vegetable industry to control norovirus and HAV without changing food quality. Highlights: ClO2 and PAA could be potential alternatives to NaOCl during fresh root vegetables washing steps. 270 ppm ClO2 or 280 ppm PAA are suitable to inactivate MNV-1 and HAV on carrot and lotus root. All disinfectants had no adverse effects on physico-chemical qualities in fresh root vegetables.